Sympatric Seals, Satellite Tracking and Protected Areas: Habitat-Based Distribution Estimates for Conservation and Management - Matt I. D. Carter; Lars Boehme; Michelle A. Cronin; Callan D. Duck; W. James Grecian; Gordon D. Hastie; Mark Jessopp; Jason Matthiopoulos; Bernie J. McConnell; David L. Miller; Chris D. Morris; Simon E. W. Moss; et al. (Frontiers in Marine Science, 2022)
Marine predator populations are crucial to the structure and functioning of ecosystems. Like many predator taxa, pinnipeds face an increasingly complex array of natural and anthropogenic threats. Understanding the relationship between at-sea processes and trends in abundance at land-based monitoring sites requires robust estimates of at-sea distribution, often on multi-region scales. Such an understanding is critical for effective conservation management, but estimates are often limited in spatial extent by spatial coverage of animal-borne tracking data. Grey ( Halichoerus grypus ) and harbour seals ( Phoca vitulina ) are sympatric predators in North Atlantic shelf seas. The United Kingdom (UK) and Ireland represents an important population centre for both species, and Special Areas of Conservation (SACs) are designated for their monitoring and protection. Here we use an extensive high-resolution GPS tracking dataset, unprecedented in both size (114 grey and 239 harbour seals) and spatial coverage, to model habitat preference and generate at-sea distribution estimates for the entire UK and Ireland populations of both species. We found regional differences in environmental drivers of distribution for both species which likely relate to regional variation in diet and population trends. Moreover, we provide SAC-specific estimates of at-sea distribution for use in marine spatial planning, demonstrating that hotspots of at-sea density in UK and Ireland-wide maps cannot always be apportioned to the nearest SAC. We show that for grey seals, colonial capital breeders, there is a mismatch between SACs (where impacts are likely to be detected) and areas where impacts are most likely to occur (at sea). We highlight an urgent need for further research to elucidate the links between at-sea distribution during the foraging season and population trends observed in SACs. More generally, we highlight that the potential for such a disconnect needs to be considered when designating and managing protected sites, particularly for species that aggregate to breed and exhibit partial migration (e.g. grey seals), or spatial variation in migration strategies. We demonstrate the use of strategic tracking efforts to predict distribution across multiple regions, but caution that such efforts should be mindful of the potential for differences in species-environment relationships despite similar accessible habitats.

Finescale ecological niche modeling provides evidence that lactating gray seals ( Halichoerus grypus ) prefer access to fresh water in order to drink - James E. Stewart; Paddy P. Pomeroy; Callan D. Duck; Sean D. Twiss (Marine Mammal Science, 2014)
Many phocids are capital breeders, relying on stored reserves to sustain energetic requirements while on land. Their large body size, high energy expenditure during lactation, and the insulative effects of the blubber layer can lead to thermal stress from overheating, especially in warm and temperate climates. Thermal stress can influence fine‐scale site choice on breeding colonies, and behavioral thermoregulation has been proposed as an explanation for the clear preferences shown by breeding female gray seals for proximity to pools of water. However, anecdotal observations suggest that pools of water may also be preferred for drinking, though water intake is difficult to verify without real‐time physiological monitoring. Here, an alternative approach demonstrates that gray seals also require access to water for drinking. Using Ecological Niche Factor Analysis to examine fine‐scale physical determinants of pupping site choice at North Rona, Scotland, we found that lactating mothers showed preference for lower salinity pools. This is most pronounced early in the season, when ambient temperatures and presumably thermal stress are greatest. Given that the cooling effect of fresh and salt water should be equivalent, the most parsimonious explanation for this preference for fresh water pools is that lactating females use these pools for drinking.

State-space modelling reveals proximate causes of harbour seal population declines - Jason Matthiopoulos; Line Cordes; Beth Mackey; David Thompson; Callan Duck; Sophie Smout; Marjolaine Caillat; Paul Thompson (Oecologia, 2014)

Region‐wide changes in marine ecosystem dynamics: state‐space models to distinguish trends from step changes - Matthew Spencer; Nova Mieszkowska; Leonie A. Robinson; Stephen D. Simpson; Michael T. Burrows; Silvana N. R. Birchenough; Eva Capasso; Polly Cleall‐Harding; Julia Crummy; Callan Duck; Damien Eloire; Matthew Frost; et al. (Global Change Biology, 2012)
Regime shifts are sudden changes in ecosystem structure that can be detected across several ecosystem components. The concept that regime shifts are common in marine ecosystems has gained popularity in recent years. Many studies have searched for the step‐like changes in ecosystem state expected under a simple interpretation of this idea. However, other kinds of change, such as pervasive trends, have often been ignored. We assembled over 300 ecological time series from seven UK marine regions, covering two to three decades. We developed state‐space models for the first principal component of the time series in each region, a common measure of ecosystem state. Our models allowed both trends and step changes, possibly in combination. We found trends in three of seven regions and step changes in two of seven regions. Gradual and sudden changes are therefore important trajectories to consider in marine ecosystems.